A hallmark of balancing selection is present at the promoter region of interleukin 10. - Wilson, J; Rockett, K; Keating, B; Jallow, M; Pinder, M; Sisay-Joof, F; Newport, M; Kwiatkowski, D (2006)
As an anti-inflammatory mediator IL10 is beneficial in certain contexts and deleterious in others. As increased production of IL10 favours protection against inflammatory disease, whereas low production promotes elimination of foreign pathogens by the host, we investigated the possible influence of balancing selection at this locus. We began by resequencing 48 European and 48 African chromosomes across 2.2 kb of the IL10 promoter region, and compared this with four neighbouring gene regions: MK2, IL19, IL20 and IL24. Analysis of nucleotide diversity showed a positive Tajima's D-test for IL10 in Europeans, of borderline statistical significance (1.89, P=0.05). Analysis of F(st) values showed significant population divergence at MK2, IL19, IL20 and IL24 (P<0.01) but not at IL10. Taken together, these findings are consistent with the hypothesis that balancing selection has played a role in the evolution of polymorphisms in the IL10 promoter region.